BTS guideline for the investigation and management of malignant pleural mesothelioma - Woolhouse, I; Bishop, L; Darlison, L; de Fonseka, D; Edey, A; Edwards, J; Faivre-Finn, C; Fennell, D; Holmes, S; Kerr, K; Nakas, A; Peel, T; et al. (BMJ Publishing Group, 2018)
The full guideline for the investigation and management of malignant pleural mesothelioma is published in Thorax. The following is a summary of the recommendations and good practice points. The sections referred to in the summary refer to the full guideline.